Molecular Mechanisms of Transdifferentiation of Adipose-Derived Stem Cells into Neural Cells: Current Status and Perspectives - Liang Luo; Da-Hai Hu; James Q. Yin; Ru-Xiang Xu (Stem Cells International)
Neurological diseases can severely compromise both physical and psychological health. Recently, adult mesenchymal stem cell- (MSC-) based cell transplantation has become a potential therapeutic strategy. However, most studies related to the transdifferentiation of MSCs into neural cells have had disappointing outcomes. Better understanding of the mechanisms underlying MSC transdifferentiation is necessary to make adult stem cells more applicable to treating neurological diseases. Several studies have focused on adipose-derived stromal/stem cell (ADSC) transdifferentiation. The purpose of this review is to outline the molecular characterization of ADSCs, to describe the methods for inducing ADSC transdifferentiation, and to examine factors influencing transdifferentiation, including transcription factors, epigenetics, and signaling pathways. Exploring and understanding the mechanisms are a precondition for developing and applying novel cell therapies.